Mitigating Precarious Employment in Quebec: The Role of Minimum Employment Standards Legislation - Bernstein, Stephanie (Precarious Employment: Understanding Labour Market Insecurity in Canada, 2006)
[A]ddresses Quebec's approach to reforming its Labour Standards Act. ...[E]xamines developments in Quebec in the early 2000s, with attention to efforts by the government to evaluate "atypical workers" in an attempt to mitigate precarious employment in this jurisdiction. –From editor's introductory chapter, p. 37.
Keywords: Labor Unions; Labor laws and legislation; Labor market; Temporary employment